Numerical Dynamic Response Analysis of a Ship Engine Room Explosion Simulation Using OpenFOAM - Zeya Miao; Yuechao Zhao; Baoyang Ye; Wanzhou Chen (Journal of Marine Science and Engineering)
Maritime safety is crucial as vessels underpin global trade, but engine room explosions threaten crew safety, the environment, and assets. With modern ship designs growing more complex, numerical simulation has become vital for analyzing and preventing such events. This study examines safety risks from alternative fuel explosions in ship engine rooms, using the Trinitrotoluene (TNT)-equivalent method. A finite element model of a double-layer cabin explosion is developed, and simulations using blastFOAM in OpenFOAM v9 analyze shock wave propagation and stress distribution. Four explosion locations and five scales were tested, revealing that explosion scale is the most influential factor on shock wave intensity and structural stress, followed by equipment layout, with location having the least—though still notable—impact. Near the control room, an initial explosion caused a peak overpressure of 2.4 × 106 Pa. Increasing the charge mass from 10 kg to 50 kg raised overpressure to 3.9 × 106 Pa, showing strong dependence of blast intensity on explosive mass. Equipment absorbs and reflects shock waves, amplifying localized stresses. The findings aid in optimizing engine room layouts and improving explosion resistance, particularly for alternative fuels like liquefied natural gas (LNG), enhancing maritime safety and sustainability.